Experimental methods in modern biotechnology (volume 2) - Jamal, Parveen (IIUM Press, 2016)
In order to fulfil the ever-growing biotechnology products in the form of, e.g. bioactive compounds for various pharmaceutical applications, promising microorganism for production of value added products and turning wastes into wealth, scientists have to resort to newer and sophisticated technology so that they could accomplish their targets without taking too copious times. Towards this end, various research methods have come into being. There are a number of books and research papers guiding and facilitating biotechnology students at all levels. In view of the facts that some writings have become obsolete and some others are very difficult for students to understand, the teaching staff of the Department of Biotechnology Engineering of the Faculty of Engineering, International Islamic University Malaysia,